Intrageneric karyotypic divergence in Scythrophrys and new insights into the relationship with Paratelmatobius (Anura, Leptodactylidae) - Lourenco, L. B.; Garcia, PCD; Recco-Pimentel, S. M. (Unione Zoologica Italiana, 2003)
Three populations of Scythrophrys from Brazil were studied cytogenetically. The karyotype found in Piraquara (Parana State) and Sao Bento do Sul (Santa Catarina State) (karyotype 1) differed from that of Rancho Queimado (Santa Catarina State) (karyotype 11) in NOR location and in the occurrence of some C-bands. In karyotype I, pair 5 contained NOR-bearing chromosomes, while in karyotype 11 the NOR occurred in pair 10. This difference probably accounts for the inverted classification of pairs 5 and 6 in these karyotypes, which appear to be homologous, as suggested by the presence of heterochromatic markers. These karyotypes also differed in the size of the non-centromeric C-bands in pairs 1 and 8. Comparison of the Scythrophrys karyotypes with those of the related genus Paratelmatobius revealed several similarities, especially between karyotype 11 of Scythrophrys and that of P. poecilogaster. Both karyotypes had a NOR in pair 10, so it was inferred to be present also in the common ancestor for these genera. The non-centromeric C-bands in pairs 7, 10, and in pair 5 of karyotype I and pair 6 of karyotype II of Scythrophrys are characters exclusively found in this genus.
Keywords: Scythrophrys; Paratelmatobius; cytogenetics; chromosome; NOR; C-band